2012
DOI: 10.4269/ajtmh.2012.12-0392
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of HIV Infection on the Risk, Frequency, and Intensity of Plasmodium falciparum Parasitemia in Primigravid and Multigravid Women in Malawi

Abstract: Abstract. Human immunodeficiency virus (HIV) is common in pregnant women in many malaria-endemic regions and may increase risk of placental parasitemia. Placental malaria is more common in primigravidae than multigravidae, but the relationship between HIV and malaria across gravidities is not well characterized. We recruited pregnant Malawian women during the second trimester and followed them until delivery. Parasitemia was assessed at enrollment, follow-up visits, and delivery, when placental blood was sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Another recent study of 32 maternal deaths in a tertiary hospital in Malawi in 2011 found that 13 (40%) of the women were HIV positive, 9 HIV negative and 10 had an unknown HIV status and classified 6 (19%) of the maternal deaths as due to sepsis and a further 3 (9%) due to HIV-related disease. 58 HIV infection may also predispose pregnant women to more severe malarial morbidity, [59][60][61] but data related to trends in malaria-related maternal complications are limited.…”
Section: Hiv Aids and Artmentioning
confidence: 99%
“…Another recent study of 32 maternal deaths in a tertiary hospital in Malawi in 2011 found that 13 (40%) of the women were HIV positive, 9 HIV negative and 10 had an unknown HIV status and classified 6 (19%) of the maternal deaths as due to sepsis and a further 3 (9%) due to HIV-related disease. 58 HIV infection may also predispose pregnant women to more severe malarial morbidity, [59][60][61] but data related to trends in malaria-related maternal complications are limited.…”
Section: Hiv Aids and Artmentioning
confidence: 99%
“…However, estimates of the global burden of congenital infections and attributable stillbirths, neonatal disease, disability or deaths due to mother-to-child transmission (MTCT) of these infections in low-income countries (LIC) are limited on account of a generalized scarcity of data[ 5 ]. Despite the positive impact in terms of health outcomes shown by the introduction of screening and treatment policies for several pregnancy-relevant infections such as human immunodeficiency virus (HIV), syphilis or malaria[ 6 , 7 ]; pathogens that may also be vertically transmitted beyond these infections are rarely the focus of clinical practice and research[ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite pregnancy-relevant infections being an intensive field of research, their causes and possible co-infections are rarely specified on the pathogenic level in these countries. Only Plasmodium and HIV (co-) infections are often in the focus of research [ 5 ].…”
Section: Introductionmentioning
confidence: 99%